Characterization and evaluation of bioformulation from antagonistic and flower inducing Trichoderma asperellum isolate UCRD5. (August 2022) - Sharma, Anu; Salwan, Richa; Kaur, Randhir; Sharma, Rhydum; Sharma, Vivek
Abstract: Trichoderma species due to their fungal plant pathogen suppression and ecofriendly nature are Trichoderma species due to their fungal plant pathogen suppression and ecofriendly nature are deployed in agriculture as biocontrol agents for the management of plant diseases in agricultural crops since a long-time. The potential biocontrol species/strains of Trichoderma from native geographic locations are often used for the effective management of various abiotic and biotic stresses in plants. Furthermore, bioformulation of biocontrol strains are often prepared using different carriers and evaluated for their effectiveness. Therefore, the isolates of Trichoderma were evaluated against plant fungal pathogens such as Fusarium oxysporum, Sclerotinia sclerotiorum, Alternaria solani and Phytophthora sp. suppression. The pot experiments carried in tomato plants inoculated with a combination of pathogens and one of the most effective Trichoderma asperellum isolate UCRD5 revealed that beside disease suppression, the biocontrol strain led to the significantly early induction of flowering in plants, compared to control. Further, characterization of talc powdered and calcium alginate based bioformulation of Trichoderma asperellum isolate revealed better shelf-life for calcium alginate based bead bioformulation. Keeping in view the difference in the biocontrol potential of Trichoderma isolates from different geographic locations, the present study explores the native isolates of Trichoderma from the agricultural fields of Punjab region, for the effective management of various abiotic and biotic stresses in agricultural crops. Further, efforts were made to enhance the shelf-life and biocontrol efficacies using sodium alginate based beads. The ability of the indigenous Trichoderma isolated to suppress plant fungal pathogens and induce flowering in tomato, coupled to encapsulated formulations with better shelf-life indicates its potential in enhancing the agricultural productivity. Highlights: Trichoderma  isolates from agricultural fields of Punjab were characterized. Trichoderma isolates were evaluated for their plant fungal pathogen suppression ability. The experimental studies also revealed the flower inducing ability of the isolate.